2004
DOI: 10.1073/pnas.0400615101
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin 1, a SCA1 neurodegenerative disorder protein, is functionally linked to the silencing mediator of retinoid and thyroid hormone receptors

Abstract: Ataxin 1 (Atx1) is a foci-forming polyglutamine protein of unknown function, whose mutant form causes type 1 spinocerebellar ataxia in humans and exerts neurotoxicity in transgenic mouse and fly expressing mutant Atx1. In this study, we demonstrate that Atx1 interacts with the transcriptional corepressor SMRT (silencing mediator of retinoid and thyroid hormone receptors) and with histone deacetylase 3. Atx1 binds chromosomes and mediates transcriptional repression when tethered to DNA. Interaction with SMRT-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 52 publications
7
130
0
Order By: Relevance
“…The gene ATXN1, which is mutated to contain an expanded CAG trinucleotide repeat in spinocerebellar ataxia-1, encodes for the protein Ataxin 1. Ataxin 1 is detected in various brain regions and in non-neuronal tissues, such as the heart, skeletal muscle and liver (Servadio et al, 1995;Tsai et al, 2004). Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…The gene ATXN1, which is mutated to contain an expanded CAG trinucleotide repeat in spinocerebellar ataxia-1, encodes for the protein Ataxin 1. Ataxin 1 is detected in various brain regions and in non-neuronal tissues, such as the heart, skeletal muscle and liver (Servadio et al, 1995;Tsai et al, 2004). Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…Two groups have confirmed the ability of ataxin-1, independent of glutamine repeat length, to repress transcription when tethered to artificial promoters (Tsai et al 2004;Okazawa et al 2002). In 2002, one of these groups showed the ability of mutant ataxin-1[82Q] to repress transcription was enhanced in the presence of PQBP-1 (polyQ-binding protein) (Okazawa et al 2002).…”
Section: Sca1: Corepressors and Remodeling At Sites Of Transcriptionmentioning
confidence: 98%
“…In addition to demonstrating ataxin-1's ability to mediate transcriptional repression and bind chromosomes, Ron Evans's group (Tsai et al 2004) showed an interaction of ataxin-1 with the corepressors, silencing mediator of retinoid and thyroid hormone receptors (SMRT) and histone deacetylase 3 (HDAC3). There was enhanced Drosophila eye neurodegeneration when SMRTER (Drosophila homolog of SMRT) and mutant ataxin-1[82Q] flies were crossed compared with mutant ataxin-1[82Q] alone (Tsai et al 2004).…”
Section: Sca1: Corepressors and Remodeling At Sites Of Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A self-association region of the non-expanded protein was mapped in the centre of the protein and identified to overlap the only certified globular domain of the otherwise PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.259v1 | CC-BY 4.0 Open Access | received: , published: 27 Feb 2014 mostly unstructured protein, the AXH domain that spans residues 562-689 (SMART SM00536) (Burright et al, 1997;de Chiara et al, 2003). This motif is functionally very important as it is involved in transcriptional regulation as well as in the RNA-binding activity of ataxin-1 (Matilla et al, 1997;Okazawa et al 2002;Tsai et al, 2004;de Chiara et al, 2003;de Chiara et al, 2005;Mizutani et al, 2005;Tsuda et al 2005;Lam et al, 2006;Serra et al, 2006;Goold et al, 2007;Lee et al 2011). AXH is also necessary and sufficient for the majority of the known interactions of ataxin-1 with other proteins, most of which are transcriptional regulators (Tsai et al, 2004;Tsuda et al 2005;Lam et al, 2006;Goold et al, 2007;Serra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%